Kontribusi Persepsi Guru Terhadap Storytelling dan Kemampuan Berpikir Kritis Anak Usia Dini - Gian Fitria Anggraini; Susanthi Pradini (Jambura Early Childhood Education Journal, 2026)
Critical thinking skills are among the most crucial 21st-century skills to develop from an early age. This study uses a correlational quantitative approach to analyze the relationship and contribution of teachers' perceptions of storytelling methods to early childhood critical thinking skills. The total sample in this study comprised 108 early childhood teachers selected through random sampling. Data collection was carried out using questionnaires. The results of the analysis showed a significant positive relationship between teacher perception and children's critical thinking skills, although the relationship was weak (r = 0.263, p = 0.006). In addition, teachers' perceptions account for only 6.9% of critical thinking skills, while the remaining 93.1% is influenced by other factors. Based on the results of the cross-table analysis, a gap between theory and practice in storytelling activities was revealed: teachers' understanding was dominated by the medium category (42.59%), even though almost all teachers strongly agreed on the urgency of storytelling. This can cause children's critical thinking skills to fail to develop optimally, as reflected in the moderate category (72.2%). This research confirms the need to reconstruct storytelling training, especially for teachers, to place greater emphasis on design techniques that highlight critical questions in storytelling activities. Kemampuan berpikir kritis merupakan salah satu keterampilan abad ke-21 yang krusial untuk dibangun sejak dini. Penelitian ini menggunakan pendekatan kuantitatif korelasional yang bertujuan untuk menganalisis hubungan serta kontribusi persepsi guru terhadap metode storytelling terhadap kemampuan berpikir kritis anak usia dini. Adapun total sampel dalam penelitian ini berjumlah 108 guru PAUD yang dipilih secara acak (random sampling). Hasil analisis menunjukkan adanya hubungan positif yang signifikan antara persepsi guru dan kemampuan berpikir kritis anak, meskipun berada pada kategori hubungan yang lemah (r = 0.263, p = 0.006). Selain itu, persepsi guru hanya memberikan kontribusi sebesar 6,9% terhadap kemampuan berpikir kritis, sedangkan sisanya 93,1% dipengaruhi oleh faktor lain. Berdasarkan hasil analisis tabel silang, terungkap adanya gap atau kesenjangan antara teori dan praktik dalam kegiatan storytelling, di mana pemahaman guru didominasi oleh kategori sedang (42,59%), meskipun hampir semua guru menyatakan sangat setuju terhadap urgensi storytelling. Hal ini dapat menyebabkan kemampuan berpikir kritis anak tidak berkembang secara optimal, yang tercermin pada kategori sedang (72,2%). Penelitian ini menegaskan adanya rekonstruksi pelatihan storytelling, khususnya bagi guru, agar lebih berfokus pada teknik perancangan yang menonjolkan pertanyaan-pertanyaan kritis selama kegiatan bercerita.